Managing the Risks of Peer-to-Peer Goods-Sharing - Sally Zhu (Law, Technology and Humans, 2022)
The peer-to-peer (P2P) goods-sharing economy has flourished into a significant economic sector. However, in the law of England and Wales, the existing legal mechanisms for managing risks to consumers, such as the Consumer Protection Act and Consumer Rights Act, are unsuitable for regulating risk in the P2P-sharing economy. Platform service providers have constructed their own risk-management systems through elaborate contracts, but these do not go far enough in protecting consumers. This paper argues that both legal and platform mechanisms face the same obstacles to scaling efficient risk management due to the atomistic way they approach risk relations. I propose that legal reforms should provide mandates on platforms to institute greater protections for their users by arranging insurance and bearing default risk.